Postpartum pneumoperitoneum: an important clinical lesson. (3rd December 2012) - Miles Dua, Sascha; Morrison, Christa; Farrant, Joanna; Rolles, Keith
Abstract : A 23-year-old primigravida presented to accident and emergency department with a 4-day history of generalised abdominal pain associated with vomiting and diarrhoea. She had previously given birth to her first child by vaginal delivery 6 days previously at another hospital and suffered a third-degree vaginal tear following prolonged labour. Shortly after birth, the patient had described the unusual symptom of soft tissue crepitations in the neck, but had been reassured and discharged without further investigation by her obstetrics team and reassured by a visiting general practitioner. At representation, the patient had obvious pneumoperitoneum, which was missed by the admitting team and underwent laparotomy for perforated duodenal ulcer.